Working with Meaning: Employee Mindfulness, Workplace Spirituality, and Innovative Work Behavior Among Employees - Sari, Nadia Nila; Ambalika, Ni Komang Ayu Diah; Azzahra, Hurul A’ini Sekar; Oktavian, Muhammad Noer; Mariyam, Mariyam (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the role of employee mindfulness in shaping workplace spirituality, job satisfaction, and innovative work behavior among employees in Indonesia. The Indonesian context, characterized by a high level of religiosity, provides a relevant foundation for examining the relationship between individual awareness, workplace spirituality, and innovative behavior within organizational settings. This study adopts a quantitative approach using a survey method involving 145 active employees from various industry sectors in Indonesia. Data were collected through an online questionnaire and analyzed using SEM-PLS with the support of SmarPLS 4 software. The results indicate that employee mindfulness has a positive and significant effect on workplace spirituality, which is found to have a positive and significant influence on innovative work behavior and job satisfaction. However, the findings reveal that employee mindfulness does not have a significant effect on job satisfaction, and job satisfaction does not significantly influence innovative behavior, which is driven more by self-awareness and a sense of meaning at work than by job satisfaction alone. Theoretically, this study extends the literature by highlighting the role of mindfulness and workplace spirituality as important psychological resources in fostering innovative work behavior, particularly in the context of developing countries. Practically, the findings imply that organizations should not focus solely on enhancing job satisfaction, but also on cultivating work environments that support awareness, meaningful work, and spirituality in order to promote sustained innovation and employee well-being.